Effective recycling of Cu from electroplating wastewater effluent via the combined Fenton oxidation and hydrometallurgy route. (1st October 2020) - Zhu, Suiyi; Wang, Zhihua; Lin, Xue; Sun, Tong; Qu, Zhan; Chen, Yu; Su, Ting; Huo, Yang
Abstract: Heavy metals, which commonly occur in complex forms, are difficult to remove in alkali electroplating wastewater effluent, and their resource recycling is rarely reported. Here, a Cu-bearing alkali wastewater effluent was effectively treated through Fenton oxidation, and the generated Fenton sludge was recycled into highly pure tenorite and hematite particles. The effluent contained 1.51 mg/L Cu and was subjected to Fenton oxidation, pH adjustment and coagulation. Amongst the three methods, Fenton oxidation showed superior efficiency to Cu removal, and the residual Cu in the effluent was 0.06 mg/L, thereby meeting the discharge standard for electroplating wastewater. However, Cu removal achieved less than 20% after pH adjustment and coagulation. Cu-bearing sludge, which was generated through the Fenton process, was dissolved in a mixture of hydrochloric and nitric acids. The dissolved solution contained 1.92 g/L Cu and 73.6 g/L Fe impurity. Impure Fe (67.4%) was removed as hematite aggregates after the solution was directly treated via a hydrometallurgy route, whilst 99.2% Cu was kept. When 0.5 mL of methanol was introduced to the hydrometallurgy system, nearly 100% Fe was removed as hematite nanoparticles with 94.8% purity, whilst more than 98% Cu was kept. The residual Cu was 1.88 g/L and precipitated as a tenorite block with a CuO content of 91.1% by adjusting the treated solution to pH 9. This study presented an environment-friendly method for enriching Cu from electroplating wastewater effluent without generating any waste. Highlights: Cu complex was removed effectively by Fenton oxidation. The generated Fenton sludge was recycled as tenorite and byproduct hematite. The byproduct hematite contained 94.8% Fe2 O3 . The product tenorite was highly purified with 91.1% CuO.